2001
DOI: 10.1037/0096-1523.27.5.1243
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of breathing and movement during manual wheelchair propulsion.

Abstract: The hypothesis of this study was that stable coordination patterns may be found both within and between physiological subsystems. Many studies have been conducted on both monofrequency and multifrequency coordination, with a focus on both the frequency and phase relations among the limbs. In the present study, locomotor-respiratory coupling was observed in the maintenance of small-integer frequency ratios (2:1, 3:1, and 4:1) and in the consistent placement of the inspiratory phase just after the onset of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 54 publications
(137 reference statements)
3
36
0
Order By: Relevance
“…Other studies have shown more stable frequency locking in experts [1,9]. However, more than expertise in term of quantity of practice, the ability to coordinate locomotion and respiration seems to be related to the aerobic capacity of individuals [2,4], a result demonstrating that the coupling between respiration and locomotion plays a role in the energy transfer.…”
Section: Link Between Expertise -Lrc -Energymentioning
confidence: 87%
“…Other studies have shown more stable frequency locking in experts [1,9]. However, more than expertise in term of quantity of practice, the ability to coordinate locomotion and respiration seems to be related to the aerobic capacity of individuals [2,4], a result demonstrating that the coupling between respiration and locomotion plays a role in the energy transfer.…”
Section: Link Between Expertise -Lrc -Energymentioning
confidence: 87%
“…However, a functional bidirectional coupling between speech and finger movement has been observed suggesting that the interaction between concurrently active effectors might better be viewed as coordination rather than interference (Chang & Hammond, 1987;Kelso, Tuller, & Harris, 1983;Whitall, 1996). A further advantage of a dynamics perspective on inter-effector coupling is that it can encompass non-intentional movements such as the vegetative processes underlying the coordination of respiration and locomotion (Amazeen, Amazeen, & Beek, 2001;Goldfield, Schmidt, & Fitzpatrick, 1999), as well as a wide range of phenomena involving the coordination of perception and action (Treffner & Morrison, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…No variation in propulsion mechanisms has been studied and up to date studies have focused on the conventional wheelchair propulsion technique and its components [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%